Exploring business doctoral students attitudes, training, and use of classroom experiential learning activities. Issue 2 (July 2021) - Bennett, Andrew A.; Lo, Kevin D.; Pervez, Adam; Nelson, Terry A.; Mullane, Kenneth; Farrell, Matthew; Wilson, Samuel; Decker, Mallory; Tarr, Emily K.
Abstract: There are growing calls both within universities and from external stakeholders to utilize experiential pedagogy in business courses. In this mixed-methods study, we use the Theory of Planned Behavior and Social Learning Theory as frameworks to investigate how business doctoral students learn about and use experiential pedagogical practices. Findings from quantitative data show that a conceptual change (student-focused) attitude towards teaching has a positive relationship with the use of experiential learning activities. Interestingly, teaching norms and pedagogical training did not have a direct relationship with these pedagogical practices. Exploring qualitative responses revealed that doctoral student pedagogical practices are influenced by other doctoral students, observing faculty teaching behaviors, their own learning experiences as students, and previous experience before the doctoral program in education and training environments. This study contributes to ongoing conversations about business pedagogical practices and business doctoral training on teaching. Limitations and possibilities for future research are discussed. Highlights: Attitudes have a direct impact on teaching practices. Students learn to teach by watching peers and other instructors. Business courses use experiential exercises more than simulations. Business courses use role play activities more than simulations.